2014
DOI: 10.1682/jrrd.2013.13.0075
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based assessment of falls risk in older veterans with executive dysfunction

Abstract: Abstract-Falling is a serious hazard for older veterans that may lead to severe injury, loss of independence, and death. While the American Geriatrics Society (AGS) provides guidelines to screen individuals at risk for falls, the guidelines may be less successful with specific subgroups of patients. In a veteran sample, we examined whether the Timed Up and Go (TUG) test, including a modified version, the TUG-Cognition, effectively detected potential fallers whose risk was associated with cognitive deficits. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…Our univariate analysis revealed a significant association between the risk of falls and the TUG-normal, TUG-dual and TUG-cognitive tests. The TUG test has been reported to identify patients at risk for falls due to cognitive impairment [48]. However, in disagreement with other studies [47,49,50,51], our multivariable analysis revealed that the TUG tests were not independently associated with the risk of falls in older adults living in the UAE.…”
Section: Discussioncontrasting
confidence: 98%
“…Our univariate analysis revealed a significant association between the risk of falls and the TUG-normal, TUG-dual and TUG-cognitive tests. The TUG test has been reported to identify patients at risk for falls due to cognitive impairment [48]. However, in disagreement with other studies [47,49,50,51], our multivariable analysis revealed that the TUG tests were not independently associated with the risk of falls in older adults living in the UAE.…”
Section: Discussioncontrasting
confidence: 98%